Deletion of Superoxide Dismutase 1 Blunted Inflammatory Aortic Remodeling in Hypertensive Mice under Angiotensin II Infusion - Yasunaga Shiraishi; Norio Ishigami; Takehiko Kujiraoka; Atsushi Sato; Masanori Fujita; Yasuo Ido; Takeshi Adachi (MDPI AG, 2021)
Superoxide dismutase (SOD) is an enzyme that catalyzes the dismutation of two superoxide anions (O2·−) into hydrogen peroxide (H2O2) and oxygen (O2) and is generally known to protect against oxidative stress. Angiotensin II (AngII) causes vascular hypertrophic remodeling which is associated with H2O2 generation. The aim of this study is to investigate the role of cytosolic SOD (SOD1) in AngII-induced vascular hypertrophy. We employed C57/BL6 mice (WT) and SOD1 deficient mice (SOD1−/−) with the same background. They received a continuous infusion of saline or AngII (3.2 mg/kg/day) for seven days. The blood pressures were equally elevated at 1.5 times with AngII, however, vascular hypertrophy was blunted in SOD1−/− mice compared to WT mice (WT mice 91.9 ± 1.13 µm versus SOD1−/− mice 68.4 ± 1.41 µm p < 0.001). The elevation of aortic interleukin 6 (IL-6) and phosphorylation of pro-inflammatory STAT3 due to AngII were also blunted in SOD1−/− mice's aortas. In cultured rat vascular smooth muscle cells (VSMCs), reducing expression of SOD1 with siRNA decreased AngII induced IL-6 release as well as phosphorylation of STAT3. Pre-incubation with polyethylene glycol (PEG)-catalase also attenuated phosphorylation of STAT3 due to AngII. These results indicate that SOD1 in VSMCs plays a role in vascular hypertrophy due to increased inflammation caused by AngII, probably via the production of cytosolic H2O2.